Knowledge about prevention and control of infection related to health care: hospital context - Andréa Mara Bernardes da Silva; Denise de Andrade; Anneliese Domingues Wysocki; Adriana Cristina Nicolussi; Vanderlei José Haas; Mário Alfredo Silveira Miranzi (Rev Rene)
Objective: to identify the knowledge of health professionals about the recommendations for prevention and control of healthcare-related infection. Methods: cross-sectional study, conducted with 308 nurses, technicians,doctors and physiotherapists in public teaching hospital. Instrument constructed and validated was used for data collection. We performed a descriptive analysis, association measures and the Student t test. Results: the comparison of means to precautions standard averages indicated that there was no significant difference between the occupational categories. The association of specific knowledge scores with time of training, performance in the institution and professional performance, show that the recommendations knowledge is different between the categories. For some professionals the more training time and professional performance, the less knowledge.A variable with respect to respiratory tract showed statistically significant (p=0.044). Conclusion: there was adequate knowledge about preventive recommendations although limited in specific fields.